Jejunal gastric heterotopia presenting as perforation peritonitis in a middle-aged adult: A case report. (March 2021) - Lee, Wonae; Jee, Ye Seob
Highlights: Jejunal gastric heterotopia rarely occurs and is usually congenital. Jejunal gastric heterotopia can be a rare cause of perforation peritonitis in adults. Our case is the presumed oldest jejunal gastric heterotopia patient presenting with perforation peritonitis ever reported. Abstract: Introduction: Gastric heterotopia rarely occurs in the small intestine beyond ligament of Treitz. Most cases of jejunal gastric heterotopia have been reported in children and young adults. Herein we report a case of jejunal gastric heterotopia presenting as a perforation peritonitis in a middle-aged adult. Presentation of case: A 51-year-old male presented with abrupt onset abdominal pain of 1 day duration. Physical examination revealed abdominal tenderness and rebound tenderness as well as costovertebral angle tenderness. Abdominal computed tomography revealed pneumoperitoneum, suggestive of hollow viscus perforation. At emergency laparotomy, a perforation site was discovered in the jejunum 100 cm distal to the ligament of Treitz. On macroscopic examination, the mucosa contained a 3 × 4 cm ill-defined, shallow ulceration next to the perforation site. Microscopically, the mucosa surrounding the perforation site revealed gastric heterotopia which consisted of gastric foveolar epithelium along with abundant pyloric glands and a few fundic glands. Discussion: To the best of our knowledge, this case is the presumed oldest jejunal gastric heterotopia patient presenting with perforation peritonitis ever reported. Conclusion: Jejunal gastric heterotopia should also be considered in the differential diagnosis of perforation peritonitis in adults.